Structure and Composition of Tree Vegetation in the High Conservation Value Area of Oil Palm Plantations - Afrianti, Suratni; Pakpahan, Enni Halimatussa'diyah (The University of Lampung, 2024)
The expansion of oil palm plantations is considered a major factor in the decline of tropical forest areas, and negatively impacting biodiversity, especially tree vegetation. This study aimed to identify tree vegetation types and the structure and composition of trees in two oil palm companies, namely PTPN IV and PTPN III. Identification of forest areas was performed by collecting data from the plantations, and processed tree species data using the quadrat method and calculated using the Shannon-Wiener and Simpson's diversity indices. Results showed that tree species with the highest Importance Value Index is Koompasia excels with a percentage of 92.95%, Shorea sp (56.7%), and Koompasia malaccensis (69.32%). Based on tree height, stratum A (>30 m) dominated in PTPN IV with 840 individual/ha, while in PTPN III-1 stratum B (20-30 m) dominated with 330 individual/ha. There were 600 individual/ha in PTPN IV with diameter class of 10-29 cm, 250 individual/ha with diameter class of 30-49 cm in PTPN III-1, and 220 individual/ha with 30-49 cm diameter in PTPN III-2. The highest Shannon-Wiener diversity index (2.148) was found in PTPN III-2, and the highest Simpson's dominance index (0.187) was found in PTPN IV. An inverted